KAJIAN PERBEDAAN PEMAHAMAN TENTANG PERTANGGUNGJAWABAN PELAKSANAAN KEGIATAN UNTUK BELANJA MAKAN MINUM (Studi Kasus pada Badan Kepegawaian Daerah Provinsi Sulawesi Utara Tahun 2013) - Subu, Supriyadi; Mawingkere, Lidya; Kalangi, Lintje (JURNAL RISET AKUNTANSI DAN AUDITING "GOODWILL", 2015)
This study aims to determine the problems in the accountability of the activities at BKD North Sulawesi, as well as to gain a shared understanding between the auditor of the Inspectorate with BKD North Sulawesi regarding accountability of eating and drinking expenditure in the designation in accordance with programs and activities that are organized in the DPA SKPD , so that there are no more errors in the document creation process of accountability by implementing activities. The object of this research is the Regional Employment Board of North Sulawesi Province and the Inspectorate of North Sulawesi province in which researchers took multiple samples among others, Treasurer Expenditure on BKD North Sulawesi province and DKP North Sulawesi Province, Head of Sub Division of Planning and Finance at BKD and DKP North Sulawesi Province, Staff At BKD, Flammable related to the functions of Treasury and Verification, Auditor and Functional Implementation Supervisory Affairs Regional Government (P2UPD) in North Sulawesi Provincial Inspectorate. Sample numbering 12 people. Data collected in the form of primary data obtained through interviews with a sample. Tesis ini using qualitative research approaches. The results showed that there are some things that a problem is found in the differences in the understanding of the accountability of the budget for eating and drinking expenditure at BKD North Sulawesi province with the auditors of the Inspectorate of North Sulawesi province. The other thing that is encountered is the problem of communication, and understanding of the regulations are still lacking.